THE IMPLEMENTATION OF EVERYONE IS A TEACHER HERE (EITH) STRATEGY TO IMPROVE THE STUDENTS' SPEAKING SKILL IN DELIVERING OPINION - Nur Aini Anisa; Eny Syatriana; Ratu Yulianti Natsir (FKIP Unismuh Makassar, 2022)
This research aimed to see the implementation of Everyone is a Teacher Here Strategy for students’ speaking skills in learning English, in terms of self-confidence. This research used a pre-experimental method. The data collection technique was taken through pre-test and post-test. The researcher was conduct at SMA Muhammadiyah 5 Makassar, with the population was the XII grade students of SMA Muhammadiyah 5 MakassarThe result of this research indicated that the average pre-test score of students before treated on self-confidence was 45 and the average score of post-test students after treatment on self-confidence was 62. The significance between pre-test and post-test was 38%. The result of data analysis showed that the improvement in students’ speaking skills after given treatments used the EITH strategy was increasing significantly. This was evidenced by the result of statistical analysis with a significant level was = 0.025 with a degree of freedom (df) = 8, t-test = 4,477 and t-table = 2,306. Based on the result of post-test data obtained as the final result, this research provided a significant improvement with the comparison of t-test > t-table which is 2.171.Based on the result of the post-test data obtained as a final result, this research improved. Finally, it can be concluded that the implementation of Everyone is a Teacher Here strategy was capable of providing a good effect on students delivering opinions, especially in speaking skills.